2014
DOI: 10.1186/1472-6823-14-75
|View full text |Cite
|
Sign up to set email alerts
|

Depression, smoking, physical inactivity and season independently associated with midnight salivary cortisol in type 1 diabetes

Abstract: BackgroundDisturbances of the circadian rhythm of cortisol secretion are associated with depression, coronary calcification, and higher all-cause and cardiovascular mortality.The primary aim of this study was to test the associations between midnight salivary cortisol (MSC), depression and HbA1c, and control for behavioural, environmental and intra individual factors with possible impact on cortisol secretion, like smoking, physical inactivity, season, medication, diabetes duration, severe hypoglycemia episode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
103
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(108 citation statements)
references
References 40 publications
1
103
0
4
Order By: Relevance
“…Cortisol is a major contributor in the development of DKA and the December peak reported previously coincides with the period of highest risk for DKA in our study. However, in a study of people with T1D, temporal variation of midnight salivary cortisol was present, with the highest levels found in spring rather than winter . Other counter regulatory hormones were not assessed in that study and interestingly no seasonal changes in HbA1c were found, as in other studies …”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…Cortisol is a major contributor in the development of DKA and the December peak reported previously coincides with the period of highest risk for DKA in our study. However, in a study of people with T1D, temporal variation of midnight salivary cortisol was present, with the highest levels found in spring rather than winter . Other counter regulatory hormones were not assessed in that study and interestingly no seasonal changes in HbA1c were found, as in other studies …”
Section: Discussionmentioning
confidence: 56%
“…However, in a study of people with T1D, temporal variation of midnight salivary cortisol was present, with the highest levels found in spring rather than winter. 22 Other counter regulatory hormones were not assessed in that study 22 and interestingly no seasonal changes in HbA1c were found, as in other studies. 9,10,22 The temporal variations in hospitalizations for acute complications have important clinical implications.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…We have previously demonstrated in these patients with T1D that depression was associated with anxiety and increased levels of midnight salivary cortisol secretion [28,29], but not with obesity [30], which indicates traits of melancholic depression [5]. The depressed patients did not exhibit lower levels of physical activity than the non-depressed [31] -as signs of lethargy -which is characteristic for atypical depression [5].…”
Section: Introductionmentioning
confidence: 79%
“…Basally, smokers demonstrate altered sal-T and sal-C compared to controls [9,106,155]. Furthermore, English and colleagues [49] reported elevated levels of total, free, and bioavailable T in smokers compared with non-smokers.…”
Section: Smokingmentioning
confidence: 99%